PENDEKATAN EKONOMI SYARIAH DALAM MENYELESAIKAN MASALAH EKONOMI AKIBAT PANDEMI COVID-19 - Nurhidayat Nurhidayat (Sekolah Tinggi Ekonomi dan Bisnis Syariah (STEBIS) Indo Global Mandiri, 2020)
Every disaster caused by a variety of natural factors such as earthquakes, floods, eruptions and disease outbreaks, always have an impact on the emergence of various economic problems. Scarcity of goods, inflation and the emergence of bad behavior of hoarding goods. These three economic problems always arise, and become a complicated problem in the economic system. The emergence of the corona virus that has swept parts of the world and Indonesia has raised these three economic problems. This study aims to provide an overview and analyze how sharia economic approaches in answering economic problems due to the co-19 pandemic. Through this Islamic economic approach, can the three economic problems be overcome. The main problem answered in this study is whether the Islamic economic approach is able to provide solutions to economic problems due to co-19. How is the Islamic economic solution in responding to economic problems as a result of co-19. This study concludes that conceptual sharia economics is indeed a solution to economic problems due to co-19. Because the sharia economics approach is conceptualized and has an orientation as a problem solving of various economic problems that can arise at any time and in any world.